Renewal and Innovation in the Emergence of Indo-European Evaluative Morphology - Nicola Grandi (Lexis: Journal in English Lexicology)
A diachronic survey in the field of the so-called evaluative morphology in some branches of the Indoeuropean family (above all Romance and Slavonic languages and Greek) reveals two different tendencies. On the one side suffixes that displayed a diminutive value in the earliest stages of these languages do not correspond to present-day diminutive suffixes. On the other side, Proto-Indoeuropean before and Latin and Ancient Greek then lacked augmentative suffixes at all, while Romance languages and Modern Greek have at their disposal some of them. So, diminutives seem a dynamic and unstable linguistic strategy, which, in the course of ages, has undergone a wide (cyclic?) renewal: the semantic function has been kept on, while the formal strategies to express it have changed. Instead, augmentatives seem to be the result of an innovation: to a sure point, a new category has been introduced and each language has had to find the means to express it. In a diachronic perspective, augmentatives seem to be a more steady linguistic strategy than diminutives. In this paper I intend at reconstructing, going backwards, the genesis of some Romance, Slavonic, and Greek diminutive and augmentative suffixes in order to single out both their semantic archetypes and possible common stages recurring in their evolutive processes.